Bank capital, adjustment and ownership: Evidence from China - Philip Molyneux; Hong Liu; Chunxia Jiang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
We investigate ownership effects on capital and adjustments speed to the target capital ratio in China from 2000 to 2012 and find that state-owned banks hold higher levels of capital than banks of other ownership types. Foreign banks are more highly capitalized than local non-state banks but under-capitalized compared with the bigger non-state banks with nationwide presence. Foreign banks adjust risk-weighted capital towards their optimal targets at a slower speed than domestic banks, while foreign minority ownership results in a faster adjustment process. Capital is positively influenced by profitability, asset diversification and liquidity risk, but negatively influenced by bank market power. Capital ratios typically co-move with the business cycle although this relationship is reversed during the crisis period due to active government intervention. Our results are robust to various modelling specifications and have important policy implications. Publication
URN:NBN:fi:bof-201411073147
Keywords: G21; G28; C32; 330; banking; capital; adjustment; ownership; China